1995
DOI: 10.1139/v95-180
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of acetylenedicarboxylic acid esters and asymmetric Diels–Alder reactions of the bis(methyl (S)-lactyl) ester

Abstract: A general method has been developed for the preparation of acetylenedicarboxylic acid esters and applied to the synthesis of both achiral and chiral esters. Diels-Alder reactions of one of the chiral esters, the bis(methy1 (S)-lactyl) ester, with various types of dienes, such as phenylbutadiene, orthoquinodimethanes, and isobenzofuran, have been investigated. Moderate asymmetric induction was observed in reactions with dienes bearing an a-hydroxyl group. In one case, an unusual solvent-induced reversal of asym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…As one can see from Table 2 (entries 1-4), an increase in the phosphine concentration does not significantly effect the yield of the desired product 8. According to recent reports, the electron rich and sterically hindered phosphines 11-14 greatly increase the rate of oxidative addition of vinylic and aryl halides to palladium(0) and prevent undesired hel la ti on.^ According to our results, phosphine 12 gives the best results with both Pd(0Ac)z and Pd(dba)2 (entries 6 and 10). We have also found that Pd(dba)z works better than Pd(0Ac)z for most of the studied phosphines (entries 5-8 versus entries 9-12).…”
Section: Resultssupporting
confidence: 66%
“…As one can see from Table 2 (entries 1-4), an increase in the phosphine concentration does not significantly effect the yield of the desired product 8. According to recent reports, the electron rich and sterically hindered phosphines 11-14 greatly increase the rate of oxidative addition of vinylic and aryl halides to palladium(0) and prevent undesired hel la ti on.^ According to our results, phosphine 12 gives the best results with both Pd(0Ac)z and Pd(dba)2 (entries 6 and 10). We have also found that Pd(dba)z works better than Pd(0Ac)z for most of the studied phosphines (entries 5-8 versus entries 9-12).…”
Section: Resultssupporting
confidence: 66%
“…Synthesis of Type 2 electron‐deficient acetylenedicarboxylates 11a–d was not a trivial task: Fischer esterifications, triazine, and carbodiimide couplings were unsuccessful, largely due to competing intramolecular Michael additions to the activated acetylenedicarboxylate intermediates . Modification of a synthetic strategy involving the protection of the electron‐poor alkyne and subsequent acid chloride formation proved successful in furnishing Type 2 alkynes (Sch. 4).…”
Section: Resultsmentioning
confidence: 99%
“…Bromination of dicyclopropylmethanol [14] with PBr 3 , followed by 1,8-diazabicyclo [5.4.0]undec-7-ene (DBU)-induced HBr elimination provided a 5 : 1 mixture of (E)-and (Z)-1-cyclopropylbutadienes 1j. Wittig olefination of (E)-cinnamaldehyde produced pure (E)-1-phenylbutadiene (E)-1k [15]. A 4 : 1 mixture of (E)-and (Z)-1-(4-methoxyphenyl)butadiene 1l was obtained in 51% yield by acid-promoted dehydratation of 1-(4-methoxyphenyl)but-3-en-1-ol, a compound resulting from the addition of allylmagnesium chloride to p-anisaldehyde [16].…”
Section: Methodsmentioning
confidence: 99%
“…Prepared according to[15] [36].Colorless oil. UV (MeCN): 278 (24200), 232 (8800), 225 (12300), 219 (12500), 209 (13800), 197 (10300).…”
mentioning
confidence: 99%